Involvement of PRIP (Phospholipase C‐Related But Catalytically Inactive Protein) in BMP‐Induced Smad Signaling in Osteoblast Differentiation. Issue 12 (8th October 2015) - Kotani, Miho; Matsuda, Miho; Murakami, Ayako; Takahashi, Ichiro; Katagiri, Takenobu; Hirata, Masato
ABSTRACT Phospholipase C‐related but catalytically inactive protein (PRIP) was first isolated as an inositol 1, 4, 5‐trisphosphate binding protein. We generated PRIP gene‐deficient mice which exhibited the increased bone mineral density and trabecular bone volume, indicating that PRIP is implicated in the regulation of bone properties. In this study, we investigated the possible mechanisms by which PRIP plays a role in bone morphogenetic protein (BMP) signaling, by analyzing the culture of primary cells isolated from calvaria of two genotypes, the wild type and a mutant. In the mutant culture, enhanced osteoblast differentiation was observed by measuring alkaline phosphatase staining and activity. The promoter activity of Id1 gene, responding immediately to BMP, was also more increased. Smad1/5 phosphorylation in response to BMP showed an enhanced peak and was more persistent in mutant cells, but the dephosphorylation process was not different between the two genotypes. The luciferase assay using calvaria cells transfected with the Smad1 mutated as a constitutive active form showed increased transcriptional activity at similar levels between the genotypes. The expression of BMP receptors was not different between the genotypes. BMP‐induced phosphorylation of Smad1/5 was robustly decreased in wild type cells, but not in mutant cells, by pretreatment with DB867, an inhibitor of methyltransferase of inhibitory Smad6. Furthermore, BMP‐induced translocation of Smad6 from nucleus to cytosol was not much observed in PRIP‐deficient cells. These results indicate that PRIP is implicated in BMP‐induced osteoblast differentiation by the negative regulation of Smad phosphorylation, through the methylation of inhibitory Smad6. J. Cell. Biochem. 116: 2814–2823, 2015. © 2015 Wiley Periodicals, Inc.